Clinical characteristics of people with cystic fibrosis and frequent fungal infection. Issue 1 (2nd November 2021) - Poore, T. Spencer; Meier, Maxene; Towler, Elinor; Martiniano, Stacey L.; Brinton, John T.; DeBoer, Emily M.; Sagel, Scott D.; Wagner, Brandie D.; Zemanick, Edith T.
Abstract: Background: Individuals with cystic fibrosis (CF) and fungal airway infection may present with fungal bronchitis, allergic bronchopulmonary aspergillosis (ABPA) or may appear unaffected despite fungal detection. We sought to characterize people with CF with frequent detection of fungi from airway samples and determine clinical outcomes. Methods: This retrospective study included individuals with CF with ≥4 lower airway cultures over a 2‐year baseline period and ≥2 years of follow‐up. We defined two groups: ≤1 positive fungus culture ( rare ) or ≥2 positive cultures during baseline ( frequent ). Clinical characteristics and outcomes were determined. Results: Between 2004 and 2016, 294 individuals met inclusion with 62% classified as rare and 38% as frequent fungi during baseline. Median follow‐up was 6 years (range: 2–9 years). Aspergillus fumigatus was the most common fungal species detected. Individuals with frequent fungi were older (13.7 vs. 11.7 years, p = .02) and more likely to have Stenotrophomonas maltophilia (35% vs. 17%, p < .001) at baseline, but did not differ in lung function or ABPA diagnosis. During follow‐up, those with frequent fungi were more likely to have chronic Pseudomonas aeruginosa and S . maltophilia . Individuals with ABPA and frequent fungi had the highest rates of co‐infection and co‐morbidities, and a trend towards more rapid lung function decline. Discussion: Fungal infection in CF was associated with frequent P. aeruginosa and S. maltophilia co‐infection even in those without ABPA. Individuals with frequent fungi and ABPA had worse outcomes, highlighting the potential contribution of fungi to CF pulmonary disease.